The Development of Indonesian Teacher Competence Questionnaire - Meicky Shoreamanis Panggabean; Karel Karsten Himawan (Universitas Ahmad Dahlan, 2016)
Abstract The enhancement of teacher’s quality is crucial, and it remains a challenge in Indonesia. As an effort to achieve a better education quality, a comprehensive reformation of the education system has to be done, especially regarding the aspect of teacher’s quality. The cultural uniqueness may impact the different values of competent teachers, make it typical to define a competence teacher from one place to another. Up to the present, there have been wide variations of the instruments used to measure teacher competence, but most are developed with regards to the western culture. Therefore, the aim of this study was to develop a culturally-sensitive instrument to assess teacher competence based on the situation of the targeted country where the teacher resides. High schools students in Jakarta and greater area participated in this study. Validity and reliability testing were performed to confirm the psychometric property of Teacher Competence Questionnaire (TCQ). It is concluded that TCQ is a valid and reliable instrument to measure teacher competence. Several limitations related to this study are discussed. Keywords: teacher competence questionnaire, teacher evaluation, quality of education